2020
DOI: 10.1002/jac5.1311
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacist services within intensive care unit recovery clinics: An opinion of the critical care practice and research network of the American College of Clinical Pharmacy

Abstract: Intensive care unit recovery clinics (ICU‐RCs) have been proposed as a potential mechanism to address the multifaceted unmet needs of intensive care unit (ICU) survivors and caregivers. The needs of this population include, but are not limited to, medication optimization, addressing physical function and psychological needs, coordination of care, and other interventions that may help in improving patient recovery and reducing the rate of preventable readmissions. The objective of this opinion paper is to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…A comprehensive medication review is the core service provided by a pharmacist in a PASC clinic. 92 , 93 This multifaceted review encompasses medication de-prescribing, initiation or restarting of drug regimens, and therapy optimisation. Whereas stress ulcer prophylaxis in the ICU is classically associated with inappropriate continuation, any medication initiated for an inpatient indication has the potential to be inappropriately continued in the outpatient setting.…”
Section: The Pasc Clinic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive medication review is the core service provided by a pharmacist in a PASC clinic. 92 , 93 This multifaceted review encompasses medication de-prescribing, initiation or restarting of drug regimens, and therapy optimisation. Whereas stress ulcer prophylaxis in the ICU is classically associated with inappropriate continuation, any medication initiated for an inpatient indication has the potential to be inappropriately continued in the outpatient setting.…”
Section: The Pasc Clinic Modelmentioning
confidence: 99%
“…Restrictions on in-person primary care in 2020 might have resulted in missed immunisations, and changes in employment status or medication insurance coverage might affect the continuation of previous drug therapy. 92 , 93 A critical care clinical pharmacist is well positioned to address these challenges as part of an interdisciplinary clinic team. 94 Pharmacists work with a medication access team to ensure affordability and appropriate access to medications.…”
Section: The Pasc Clinic Modelmentioning
confidence: 99%
“…A recent opinion paper identi ed and described services for the management of ICU survivors and support of their caregivers in intensive care unit recovery clinics (ICU-RCs). The paper concluded that an interprofessional team in ICU-RCs can play a vital role to promote education on as post-intensive care syndrome (PICS), improve medication adherence, ensure comprehensive medication management and medication reconciliation, provide assessment of inappropriate and appropriate medications after hospitalization, and address adverse drug events (ADEs) 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent retrospective data supports the presence of pharmacists to provide medication management 11,12 . Based on this evidence, the American College of Clinical Pharmacy (ACCP) Critical Care Practice Research Network (PRN) recommended that pharmacists should be involved in ICU‐RCs and provided guidance in developing pharmacist services in ICU‐RCs 9 . Overall, ICU‐RC pharmacists are positioned to promote medication safety, efficacy and adherence 3,9,11‐15 …”
Section: Introductionmentioning
confidence: 99%